Polarization-dependent ultrafast plasmon relaxation dynamics in nanoporous gold thin films and nanowires. (22nd March 2019) - Peckus, Domantas; Chauvin, Adrien; Tamulevičius, Tomas; Juodėnas, Mindaugas; Ding, Junjun; Choi, Chang-Hwan; El Mel, Abdel-Aziz; Tessier, Pierre-Yves; Tamulevičius, Sigitas
Abstract: Metal materials structured at nanoscale are extensively used in a variety of applications, including molecular sensing, nanoscale heaters for photothermal therapy, etc. These applications depend on the strong absorption and electric field enhancements associated with localized surface plasmon resonance (LSPR). Despite multiple investigations of LSPR relaxation dynamics in plasmonic metallic nanoparticles (i.e. nanospheres, nanocubes, etc), no detailed studies of porous thin films or nanowires have been reported so far. In this paper, LSPR relaxation dynamics of nanoporous gold thin film, gold nanowires, and nanoporous gold nanowires (structures with the potential for a vast range of sensing and optical applications) were studied by means of transient absorption spectroscopy (TAS). Au and Au/Cu thin films produced by magnetron sputtering deposition over a nanograted silicon substrate enabled the creation of highly organized nanowire arrays of centimetres length. Nanoporous structures were created by the dealloying of Au/Cu alloy. We found that formation of such a subwavelength period grating structure in gold increases the efficiency of hot electron relaxation compared to continuous film, while the porosity of gold nanostructures has the opposite effect. The results also expressed a clear dependence of the TAS signal on the polarization (i.e. orientation of the electric field with respect to the nanoporous gold nanowires) of the pump and probe pulses, compared to non-porous gold nanowires.